Crustacean meal in laying hen rations. Effect on the physical quality of the egg stored in different conditions - Carranco, M. Elena; Calvo, M. de la Concepci?n; Carrillo, Silvia; Ram?rez, Rebeca; Morales, E.; Sangin?z, Leonor; Fuente, B.; ?vila, E.; P?rez-Gil, F. (Cuban Journal of Agricultural Science, 2011)
In order to find out the effect of shrimp meal (SM) and red crab meal (RCM) on fresh and stored eggs, 135 hens were used and distributed in three treatments: control, SM (20 %), and RCM (4 %). After four weeks, eggs were collected from each treatment to evaluate their physical quality at 0, 15, and 30 d/4? and 20 ?C. The results were analyzed according to 3 x 3 x 2 factorial design, and the difference between means, by the multiple range test of Duncan. The highest values were for the Haugh units in the three treatments at 0 d/20 ?C. The yolk color diminished with the SM and the RCM, at 15 and 30 d (20 ?C). The eggshell thickness decreased at 30 d/4 ?C (P < 0.05). The pH increased in time. It was concluded that the physical quality of the egg was affected by the storage time and temperature, and not by the inclusion of the Crustacean meals. Key words: Crustacean meal, egg physical quality, storage.